Case report: Artery of Percheron infarction as a rare complication during atrial fibrillation ablation - Xie, Xin; Wang, Xuecheng; Yu, Jinbo; Zhou, Xiaoqian; Shi, Liya; Zhou, Jian; Wu, Yizhang; Chen, Zijun; Zhang, Baowei; Li, Xiaorong; Yang, Bing (Frontiers in Cardiovascular Medicine, 2022)
The incidence of stroke or transient ischemic attacks (TIA) in atrial fibrillation (AF) catheter ablation procedures is around 1% and may be unnoted under anesthesia. The artery of Percheron (AOP) infarction is a rare kind of stroke with heterogeneity in manifestation, which further makes the perioperative early detection and diagnosis a challenge. Herein, we present one patient who underwent AF ablation and presented mental status alteration after withdrawing anesthetics. An emergency head CT was obtained, which revealed no apparent pathological changes. A late MRI test confirmed the diagnosis of AOP infarction. With oral anticoagulants and rehabilitation therapies, the patient’s awareness improved and fully recovered on the sixth-month follow-up. Variability in manifestation, no positive radiological finding on initial CT, and a low incidence has made few clinicians to gain much experience with this type of infarct, which delays the diagnosis and initiation of appropriate treatment.